A new model for the effect of pH on microbial growth: an extension of the Gamma hypothesis - Lambert, Ronald J. W. (Blackwell Publishing Ltd, 2011)
Aims: To investigate the appropriateness of the extended Lambert-Pearson model (ELPM) to model the effect of pH (as hydrogen and hydroxyl ions) over the whole biokinetic pH range in comparison with other available models. Methods and Results: Data for the effect of pH on microbial growth were obtained from the literature or in-house. Data were examined using several models for pH. Models were compared using the residual mean of squares. Using the ELPM, pH was modelled as hydrogen ions and hydroxyl ions; hence, the model was monotonic in each. The ELPM was able to model data more successfully than the cardinal pH model (CPM) and other models in the majority of cases. Conclusions: Examining the effect of pH as hydrogen and hydroxyl ions has the advantage that the basic form of the ELPM can be retained as each is treated as a distinct antimicrobial effect. With the ELPM, each inhibitor is described by two parameters; from these parameters, the pH(min), pH(opt) and pH(max) can be obtained. Furthermore, the idea of a dose response, absent from other models, becomes important. Significance and Impact of the Study: The CPM is an excellent model for certain situations - where there is a high degree of symmetry between the suboptimal pH and superoptimal pH response and where there are few data points available. The ELPM is more amenable to highly asymmetric behaviour, especially where plateaus of effect around the pH optimum are observed and where the number of data points is not restrictive.
Keywords: cardinal parameters hurdles predictive modelling decision-support system listeria-monocytogenes acid concentration lactic-acid temperature spoilage prediction foods